Optimizing the Imposition of Conditional Sentences for Children Through the Role of Community Research Reports - Mahrunnisa, Desy Rizky; Rasdi, Rasdi (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Punishment of children in conflict with the law requires an approach that is not only repressive but also considers the rights and future of children. A conditional sentence is a form of alternative punishment that can maintain children in a proper social environment without serving a criminal period in a correctional institution. This article examines the urgency of applying conditional punishment in juvenile cases and highlights the strategic role of community research reports in influencing judges' decisions. This research uses a qualitative method with an empirical juridical approach through field observations, literature studies, and interviews. The results show that the quality of recommendations is the primary key to successful conditional sentences in court. Data-based recommendations that address the dimensions of supervision, environmental support, and the effectiveness of non-agency coaching tend to be more accepted by judges. The optimization of conditional punishment requires increasing the capacity of community supervisors, national standardization of reports, and evaluation and feedback mechanisms from law enforcement officials to ensure the quality of recommendations submitted.